Transactional risk assessment-based approach for service degradability management - Hammadi, Adil; Hussain, Omar (IEEE Computer Society, 2011)
Service Level Agreement (SLA) has its application in Service-Oriented Computing, Grid Computing and Cloud Computing. SLA sets a benchmark against which the Quality of Service (QoS) a service provider is assessed. This assessment can be pre-interaction, post-interaction or during service delivery. QoS assessment during service delivery helps in decision making to select alternate service in case a service degrades below a given benchmark. This is particularly helpful in Cloud Computing where sometimes decisions need to be taken on the fly to avoid complete failure of service and to meet business needs. In this paper we use Risk Assessment to assess QoS during service delivery. In the literature, approaches have been proposed that allow for service re-composition in SOA but in Cloud Computing techniques are needed that assist in making informed service management decision. Since, similar to SOA, Cloud has self-serve autonomous mechanism, informed service management decision will help in Cloud service re-composition.